Digital Modeling of Economic Processes and Supply Chain Management in the Formation of Cooperative Relations in the Petrochemical Cluster of the Region - I.L Beilin; V.V Homenko; D.D Aleeva (International Journal of Supply Chain Management, 2019)
Abstract- A study of the state of the theory of fuzzy sets shows that until recently in Russia there were almost no studies in the chemical sector of the economy and finance using fuzzy analysis and forecasting, although by that time all necessary prerequisites for modeling financial systems had been created. The current situation in Russia is characterized by a high degree of science lagging behind the requests of state and commercial supply chain management.Fuzzy sets have not been used to date for financial analysis and planning of chemical corporations, evaluating the investment attractiveness of securities, optimizing the stock portfolio, forecasting stock indices and macroeconomic indices. You can also talk about the lack of software based on fuzzy models, although abroad, such software products and information technologies that solve economic problems using fuzzy-plural and related descriptions already exist.In the 80's, software solutions and information technologies began to emerge, solving economic problems using fuzzy-plural and related descriptions. Thus, under the leadership of C. Zopounidis at the Technical University on the island of Crete, an expert system was developed for detailed financial analysis of corporations. A little earlier in Germany, a group led by H. Zimmerman developed a strategic planning system, in which the positioning of the corporation's business is based on fuzzy descriptions of the competitiveness and attractiveness of the business.As an example of such software, you can use expensive complex systems, which include fuzzy logic, which bankers and financiers use to solve the most complicated problems of forecasting financial indicators. The beginning of this process was laid by the Japanese financial corporation. Having set out to automate the game on the securities market, this company attracted about 30 specialists in artificial intelligence.